De l’indigénisation soviétique au panturquisme académique - Marc Toutant (European Journal of Turkish Studies)
Being the classical language of the Turkic speaking peoples of Central Asia, Chaghatay Turkish and the literature that gave it its fame were subjected to cultural claims both in Soviet Uzbekistan and in the young Republic of Turkey. The specific case of the poet ‘Alī Shīr Nawā’ī (1441-1501) revealed the competition that existed between these two types of reappropriation. The Soviet policy of indigenization had led to make the Chaghatay writer an “Uzbek poet” and as such, a symbol of Uzbek national identity. In Turkey too, nationalistic interests incited scholars to regard the Timurid polymath as a “Turkish poet” and a spearhead of Turkishness. Nonetheless, beyond the academic controversies about how to describe Nawā’ī and his language from an ethnic point of view, it was obvious that Turkish scholars still heavily relied on the studies of their Soviet counterparts at the end of the 1960’s. Actually, a real transfer of knowledge was at work, which concerned all the aspects related to the study of the poet, including those that clearly bore the stamp of Soviet ideology. This process therefore brought out the fundamental ambiguity of Turkish Turcology at that time, and showed the limits of this discipline as regards its drive towards empowerment.